2013
DOI: 10.1007/s11432-013-5041-0
|View full text |Cite
|
Sign up to set email alerts
|

On the developments and applications of optical microcavities: an overview

Abstract: Devices based on the optical microcavities which confine light to small volumes by resonant recirculation are already indispensable for a wide range of studies and applications. This article provides an overview of the development and application of optical microcavities. We first give a pedagogical introduction to the interaction between a two-level system and a quantized electromagnetic field in the cavity, based on the so-called Jaynes-Cummings model, which is basic and important theory model in the cavity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 165 publications
(206 reference statements)
0
3
0
Order By: Relevance
“…Of the two herb extracts tested in this study, forsythia exhibited high antibacterial activities against both of bacterium, taraxacum only showed antibacterial activities against S. aureus. Ethanolic extracts of the compound Chinese medicine with the proportion of the honeysuckle: forsythia: the licorice as 2:2:1 were shown antivirus and antibacterial properties, S. aureus, E. coli and Candida albicans were effectively inhibited by them 8 . The activity test indicated that only ethanol extracts of Taraxacum mongolicum exhibited antibacterial activity against some bacteria, such as S. aureus and its isolated strain from air, E. coli and P. aeruginosa 9 .…”
Section: Relationship Between Antibacterial Activity and Antibiotic Cmentioning
confidence: 99%
“…Of the two herb extracts tested in this study, forsythia exhibited high antibacterial activities against both of bacterium, taraxacum only showed antibacterial activities against S. aureus. Ethanolic extracts of the compound Chinese medicine with the proportion of the honeysuckle: forsythia: the licorice as 2:2:1 were shown antivirus and antibacterial properties, S. aureus, E. coli and Candida albicans were effectively inhibited by them 8 . The activity test indicated that only ethanol extracts of Taraxacum mongolicum exhibited antibacterial activity against some bacteria, such as S. aureus and its isolated strain from air, E. coli and P. aeruginosa 9 .…”
Section: Relationship Between Antibacterial Activity and Antibiotic Cmentioning
confidence: 99%
“…The WGM resonator binds the photons inside the cavity, causing them to continuously circulate inside the cavity and thus accumulate energy [12]. Its inherent high Q factor makes the photons circulate inside the cavity for a longer period, thus enhancing the light-matter interaction [13][14][15]. In recent years, WGM resonators have been rapidly developed in the field of acoustic sensing, and a variety of acoustic sensors with excellent performance have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…And it has been widely demonstrated in nanophotonic devices, such as in the plasmonic devices and optical microcavities. Recently, optical microcavities have been extensively studied due to their advantages in isolating modes that meet specific conditions from the continuous mode by resonance and confining them to a small volume on the order of micrometers [1], [2]. Usually, there are several typical configurations of optical microcavities, such as the Fabry-Perot microcavities [3], whispering-gallery mode (WGM) optical microcavities [4]- [10], distributed feedback (DFB) microcavities [11], and photonic crystal microcavities [12].…”
Section: Introductionmentioning
confidence: 99%